2008
DOI: 10.1007/s12031-008-9091-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ganglion Cell Death by PACAP Following Optic Nerve Transection in the Rat

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide that was first isolated from the ovine hypothalamus. PACAP has previously been shown in in vitro experiments to have neuroprotective effects, but its possible application in clinical situations must first be tested in vivo. We examined the protective effect of PACAP against retinal ganglion cell (RGC) death following optic nerve transection in the rat. Fourteen days after sectioning of the optic nerve, the number of RGCs in the vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…A similar role of PACAP in the eye has also been reported, and we have previously demonstrated that PACAP prevents the retinal ganglion cell death induced by optic nerve transection in the rat (Seki et al 2008). However, the retinoprotective actions of PACAP in response to high intraocular pressure remain unclear.…”
Section: Introductionsupporting
confidence: 74%
“…A similar role of PACAP in the eye has also been reported, and we have previously demonstrated that PACAP prevents the retinal ganglion cell death induced by optic nerve transection in the rat (Seki et al 2008). However, the retinoprotective actions of PACAP in response to high intraocular pressure remain unclear.…”
Section: Introductionsupporting
confidence: 74%
“…PACAP has been shown to have various effects in the retina and in the retinal pathways (Atlasz et al 2007(Atlasz et al , 2008(Atlasz et al , 2009Babai et al 2005Babai et al , 2006Racz et al 2006aRacz et al , b, 2007Seki et al 2006Seki et al , 2008. PACAP protected all inner retinal layers, in correlation with previous results showing the distribution of PAC1 receptor in the retina (Seki et al 2000).…”
Section: Discussionsupporting
confidence: 87%
“…In vivo, PACAP counteracts the damaging effects of kainate, hypoperfusion, optic nerve transection and UVAinduced degeneration (Atlasz et al 2007, Atlasz et al 2010aSeki et al 2006Seki et al , 2008. We have provided several lines of evidence that PACAP is protective in MSG-induced retinal lesion (Tamas et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Seki et al [ 88 ] reported that optic nerve trauma resulted approximately 55 % loss of cells in the GCL. In this model, the number of cells in the GCL in animals treated before the operation with PACAP1-38 at 10 and 100 pmol in 3 μl saline (dose-dependent) intravitreally, was signifi cantly increased compared with the control group on the 14th day after surgery [ 88 ], providing evidence that PACAP is protective in this injury model.…”
Section: Optic Nerve Injury In the Retinamentioning
confidence: 99%